PUPILLONET: SUPPORT VECTOR MACHINE FOR GENETIC DISEASES DETECTION IN PAEDIATRIC AGE - J. Prashanthi (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
PUPILLONET: SUPPORT VECTOR MACHINE FOR GENETIC DISEASES DETECTION IN PAEDIATRIC AGE